Ibn ‘Arabi's Theory of Divine Roots and the Question of God and Ten Categories - Shahzad, Qaiser (Islamic Studies, 2012)
This paper constructs a theory from some of the writings of Ibn ‘Arabi (d. 1240) regarding the relationship between God and the Created nature, called “theory of divine roots.” According to this view particular ontological divine roots can be discerned for each and every facet of the created world. We appeal to this theory in order to make sense of Ibn ‘Arabi’s position regarding the possibility and meaning of the applicability of Aristotelian ten categories to God. The article starts, however, with Ibn ‘Arabi’s understanding of the categories and argues for the reconciliation of the two seemingly contradictory positions of Ibn ‘Arab┘ on the issue: first, his initial dislike of the whole discussion, and then, his own attempts to relate God to the specific categories. If we keep in mind the direct predication of any of these categories to God, then Ibn ‘Arabi most probably would negate any relation, but if we are thinking of explaining how they apply to the world with the help of divine nature then Ibn ‘Arabi is more positive.